Respuesta :

Answer:

1. The equation has 2 solutions 3. p = 0, p = -2

Step-by-step explanation:

1. The quadratic equation is ax^2+bx+c=0 [tex]x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]

in the equation a = 2, b = 3 and c = 5

so the equation would be [tex]x_{1,\:2}=\frac{-(-3)+ \sqrt{(-3)^2-4*2*5}}{2*2}[/tex]

[tex]x_{1,\:2}=\frac{3+\sqrt{9-4*2*5}}{2*2}[/tex]

simplify

[tex]3+\sqrt{31}i[/tex]

divide by 4

[tex]\frac{3}{4} +\frac{\sqrt{31} }{4}i[/tex] or [tex]x=\frac{-\left(-3\right)-\sqrt{\left(-3\right)^2-4\cdot \:2\cdot \:5}}{2\cdot \:2}:\quad \frac{3}{4}-i\frac{\sqrt{31}}{4}[/tex]

3. 4p(5p + 10) = 0 Using the Zero Factor Principle aka. zero-product property If a*b=0 then a=0 or b=0 or both a=0 and b=0

p = 0

5p + 10 = 0

subtract ten from both sides

5p = -10

divide by 5

p = -2